The impact of the training elements done by PIMMAG PD base toward customer satisfaction / Nur Izzati Zulbaharin - Zulbaharin, Nur Izzati (Faculty of Business and Management, 2015)
The purpose of study is to define the impact of training elements done by PIMMAG PD Base toward customer satisfaction. Currently, the number of members of PIMMAG keep increasing because of their satisfaction towards PIMMAG. So, in this research helped PIMMAG to know their customer level of satisfaction. The method use was non-probability sampling which is convenience sampling because it is quick and easy. The objective of this study is to identify the level of customer satisfaction in PIMMAG PD Base, to identify the relationship between training element and customer satisfaction, to identify the most dominant of training element towards customer satisfaction at PIMMAG PD Base and lastly to identify the alternative to improve customer satisfaction at PIMMAG PD Base. The result show the reliability test, demographic profile such as gender, company represented, current position, race and their experience in training as well as the level of customer satisfaction, the relationship between training element and customer satisfaction and also the most dominant training element.